BRAF V600E and lymph node metastases in papillary thyroid cancer - Chen, Pan (Endocr Connect, 2020)
OBJECTIVE: To evaluate the relationship between the BRAF V600E mutation in lymph node metastasis (LNM) and its invasive characteristics in papillary thyroid cancer (PTC). MATERIAL AND METHODS: A total of 373 PTC patients were enrolled in this study conducted at Zhujiang Hospital of Southern Medical University between January 2017 and December 2018. PTCs with cervical lymph node metastases were verified pathohistologically, and primary tumors and LNM were examined for the BRAF V600E mutation. Patients were excluded from the study if the BRAF V600E mutation was examined only in primary tumors or only in LNM. RESULTS: Of the 373 patients examined, BRAF V600E mutation frequency in primary tumors was slightly higher than in LNM (81.5% vs 78.0%, P = 0.000), the intra-class correlation coefficient (ICC) was 0.865 (95% CI 0.835–0.890). The BRAF V600E mutation in both primary tumor and LNM negatively correlated with the size of the largest metastatic focus of LNM (Odds ratio, OR = 0.297, 95% CI 0.143–0.616, P = 0.001; OR = 0.242, 95% CI 0.119–0.492, P = 0.000, respectively). There was no relationship between BRAF V600E mutation in LNM and the number, extranodal extension or stage of LNM (P > 0.05). CONCLUSION: The BRAF V600E mutation in LNM may not be related to the invasive characteristics of LNM in PTC.